2016
DOI: 10.1186/s40064-016-2008-9
|View full text |Cite
|
Sign up to set email alerts
|

Survival in patients with non-metastatic breast cancer treated with adjuvant trastuzumab in clinical practice

Abstract: PurposeThe NSABP Trial B-31 and NCCTG Trial N9831 (B-31/N9831 trials, Romond et al. in N Engl J Med 353:1673–84, 2005. doi:10.1056/NEJMoa052122; Perez et al. in J Clin Oncol 32:3744–52, 2014. doi:10.1200/JCO.2014.55.5730) established the efficacy of adjuvant trastuzumab for patients with HER2-positive early stage breast cancer. We aimed to estimate the overall survival (OS) and relapse-free survival (RFS) of HER2-positive non-metastatic breast cancer patients treated with adjuvant trastuzumab in a clinical pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
1
8
0
3
Order By: Relevance
“… 43 The 4-year relapse-free survival rate in MBC was 76%. 50 An Italian study found no difference in OS (HR 0.79 (95% CI 0.50 to 1.26)) between metastatic patients previously treated with trastuzumab for EBC who are subsequently treated with trastuzumab for MBC and patients first diagnosed with MBC receiving trastuzumab for MBC. 42 An Australian study of patients with HER2-positive MBC estimated a median OS of 29.9 months.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“… 43 The 4-year relapse-free survival rate in MBC was 76%. 50 An Italian study found no difference in OS (HR 0.79 (95% CI 0.50 to 1.26)) between metastatic patients previously treated with trastuzumab for EBC who are subsequently treated with trastuzumab for MBC and patients first diagnosed with MBC receiving trastuzumab for MBC. 42 An Australian study of patients with HER2-positive MBC estimated a median OS of 29.9 months.…”
Section: Introductionmentioning
confidence: 97%
“…Population-based study estimates of survival outcomes for women receiving HER2-targeted therapies are within the range of pivotal clinical trial estimates. Several studies reported 4-year survival rates in patients with early BC (EBC) at ∼90% 41 50 and in patients with MBC at 41%. 43 The 4-year relapse-free survival rate in MBC was 76%.…”
Section: Introductionmentioning
confidence: 99%
“…No difference in median overall survival (OS) between trial and non-trial patients was observed in similar retrospective studies in colorectal and breast cancer [7,8]. In a study performed in men with metastatic castration resistant prostate cancer, it has been demonstrated that treatment in daily practice is associated with a shorter survival and more toxicity compared with men treated in a clinical trial [9].…”
Section: Introductionmentioning
confidence: 98%
“…According to previous studies, mastectomy is an effective treatment for breast cancer, and it has been demonstrated that a bilateral risk-reducing mastectomy decreases the risk of invasion and metastases in patients with breast cancer by up to 90% (19,20). Based on a review of the literature, almost 20% of all breast cancers are HER2-positive, and one of the monoclonal antibodies against the HER2 receptor is trastuzumab, which has been used for HER2-positive breast cancers as an adjuvant treatment and target therapy (21,22). SCC may present with smooth or hyperkeratotic lesions, abscesses, nodules and ulceration of the skin, although nipple discharge is uncommon (23,24), and the symptoms of invasive ductal carcinoma are lumps, itching, burning and pain (25).…”
Section: Discussionmentioning
confidence: 99%